A Late Pleistocene Wetland Setting in the Arid Jurf ed Darawish Region in Central Jordan - Mischke, Steffen; Lai, Zhongping; Faershtein, Galina; Porat, Naomi; Röhl, Matthias; Braun, Paul; Kalbe, Johannes; Ginat, Hanan (Frontiers in Earth Science, 2021)
Current conditions in the southern Levant are hyperarid, and local communities rely on fossil subsurface water resources. The region provided a pathway for the migration of humans out of Africa and their spread in the Near East and beyond in the Pleistocene. However, times of more favourable wetter periods and also their spatial characteristics are not yet well constrained. To improve our understanding of past climate and environmental conditions in the deserts of the southern Levant, sedimentary sections including artefact-bearing beds from Jurf ed Darawish on the Central Jordanian Plateau were investigated using sedimentological and micropalaeontological analyses and OSL dating. Grain-size analysis and structures of the clayey-silty sediments show that they mainly represent reworked loess deposits. The OSL age data suggest that these fine-grained sediments were accumulated during Marine Isotope Stages (MIS) 5-3. The prevailing aggradational setting was replaced by an erosional setting sometime after 30 ka. Recorded ostracod valves (mostly Potamocypris, Ilyocypris and Pseudocandona), remains of aquatic and terrestrial gastropod shells, and charophyte gyrogonites and stem encrustations indicate that an in-stream wetland existed at the location of Jurf ed Darawish during MIS 5-4 which was replaced by a vegetated alluvial plain in MIS 3. Abundant artefacts, distributed over a vertical range of up to 40 cm in a bed covered by a sedimentary sequence of 12-m thickness, provide evidence for the presence of humans in the region during a relatively long period from ca. 85-65 ka. The reconstruction of an in-stream wetland at Jurf ed Darawish, and the presence of humans at the site and in other desert regions of the Jordanian Plateau, the Wadi Arava/Araba, and the Negev and the Nefud deserts, show that the regional climate in the late MIS 5 and MIS 4 was significantly wetter and provided favourable conditions for humans in the Southern Levant and the northwestern Arabian Peninsula.